Foreign exchange exposure of Indonesian listed firms - Mohamad, Azhar; Anisak, Nurul (Sage Publishing, 2019)
Foreign exchange exposure or exchange rate exposure is the risk that a firm’s cash flows and earnings may be affected by exchange rate movements. For multinationals that have several subsidiaries overseas, exchange rate movements may have an adverse effect on a huge number of contractual transactions. The exchange rate movements may have an impact on future cash flows, generated by the firm’s production and marketing operations. For example, a rising Indonesian rupiah may result in Indonesian goods becoming more expensive, leading to Indonesian exporters selling less in the future, resulting in unfavourable future cash flows. Lower future cash flows mean the firm’s stock valuation may decline and investors may not be attracted to investing in the firm’s stock. In this paper, we examine the effect of exchange rate movements on Indonesian listed firms’ stock prices using a multivariate model with six bilateral exchange rates. We further add a generalized autoregressive conditional heteroskedasticity (GARCH (1,1)) model for each of 100 Indonesian listed firms’ monthly closing prices from the period of January 1994 through to November 2015, and the GARCH (1,1) results are summarized and presented in Tables 1–4, 7 and 8. We find a total of 80 per cent of our sample firms to have significant exchange rate exposure. The overall results show that most of the Indonesian listed firms under study are exposed to Japanese yen, Great Britain pound and Malaysian ringgit. We posit that this sensitivity of their stock prices may be due to the fact that most of these Indonesian firms are net importers. Interestingly, the agricultural sector comes out as the most stable sector, having the least exposure and exhibiting stable performance during the Asian financial crisis of 1997/1998. For overall exchange rate exposure across all firms, we run a pooled generalized least squares model. We find that the exchange rate exposure of the Indonesian sample firms is time-variant, or in other words, very much dependent on the subperiods (before crisis, during crisis and after crisis) under study.